Sapling growth rates reveal conspecific negative density dependence in a temperate forest. Issue 19 (18th August 2017) - Ramage, Benjamin S.; Johnson, Daniel J.; Gonzalez‐Akre, Erika; McShea, William J.; Anderson‐Teixeira, Kristina J.; Bourg, Norman A.; Clay, Keith
Abstract: Local tree species diversity is maintained in part by conspecific negative density dependence (CNDD). This pervasive mechanism occurs in a variety of forms and ecosystems, but research to date has been heavily skewed toward tree seedling survival in tropical forests. To evaluate CNDD more broadly, we investigated how sapling growth rates were affected by conspecific adult neighbors in a fully mapped 25.6 ha temperate deciduous forest. We examined growth rates as a function of the local adult tree neighborhood (via spatial autoregressive modeling) and compared the spatial positioning of faster‐growing and slower‐growing saplings with respect to adult conspecific and heterospecific trees (via bivariate point pattern analysis). In addition, to determine whether CNDD‐driven variation in growth rates leaves a corresponding spatial signal, we extended our point pattern analysis to a static, growth‐independent comparison of saplings and the next larger size class. We found that negative conspecific effects on sapling growth were most prevalent. Five of the nine species that were sufficiently abundant for analysis exhibited CNDD, while only one species showed evidence of a positive conspecific effect, and one or two species, depending on the analysis, displayed heterospecific effects. There was general agreement between the autoregressive models and the point pattern analyses based on sapling growth rates, but point pattern analyses based on single‐point‐in‐time size classes yielded results that differed markedly from the other two approaches. Our work adds to the growing body of evidence that CNDD is an important force in temperate forests, and demonstrates that this process extends to sapling growth rates. Further, our findings indicate that point pattern analyses based solely on size classes may fail to detect the process of interest (e.g., neighborhood‐driven variation in growth rates), in part due to the confounding of tree size and age. Abstract : Conspecific negative density dependence (CNDD) occurs in a variety of forms and ecosystems, but research to date has been skewed towards tree seedling survival in tropical forests. We investigated how sapling growth rates were affected by large conspecific and heterospecific neighbors in a fully mapped temperate forest, and found that negative conspecific effects were stronger for most species. Our work adds to the growing body of evidence that CNDD is a major organizing force in temperate forests and demonstrates that this process extends to sapling growth rates.